The Effect of Global Awareness on Students' Reading Skill Based on Aksi Data - Susetyo, Budi; Rachman, Nurul Aulia; Rahmawat, NFN (Pusat Asesmen dan Pembelajaran, 2020)
The Indonesian Student Competency Assessment (Asesmen Kompetensi Siswa Indonesia-AKSI) is a national survey aims to monitor the quality of education system across provinces. The results of the AKSI are expected to provide inputs on policies to improve the quality of learning outcomes in particular and the quality of education in general. The objective of AKSI is to measure students’ cognitive abilities, which include science, mathematics and reading. In addition, AKSI also collects data through questionnaires, one of which is about Global Awareness. The purpose of this study was to analyze the influence of student gender, parent’s education level, interest studying other cultures, adaptability and communication, understanding of global problems, tolerance, environmental awareness and school quality on students’ reading literacy skill. The data used in this study are data from the 2019 AKSI survey of 15.738 grade IX students and school accreditation of 1.805 junior high schools in Indonesia. The results of parameter estimation and hypothesis testing using the multilevel regression model concluded that gender, father's education, adaptability and communication skills, understanding of global problems, tolerance of religious and cultural differences and school quality affect students’ reading ability.